Application of Offshore HDPE Pipes Route Design in North Maluku Indonesia - Franto Novico; Indra Kurniawan; Andi Egon; Davide Merli (Marine Science Department Diponegoro University, 2021)
The lack of fresh water for the inhabitants of Maitara island is a very urgent problem to be solved. Two main factors at least must be taken into account to deliberate the right of way of subsea High-density polyethylene (HDPE) pipes, namely the hydrodynamic conditions and of a block analysis. This paper presents the study to justify the best route of subsea HDPE pipes based on hydrodynamic model analysis and concrete block strategy. The method used to analyze the best route includes 2 aspects. Firstly, the investigation method consisting of a bathymetric survey conducted by a single beam echosounder, 15 days tidal observations and seabed sediment sampling. Secondly, the hydrodynamic modelling analysis using Mike 21 FMHD and concrete block analysis, all these studies have been completed in August 2018. In the morphological behaviour analysis, three alternative routes are considered for the subsea HDPE pipes from Tidore Island to Maitara Island. The outcome of the analysis shows that the second track line option has the smallest impact by the hydrodynamic conditions, with a current speed of less than 0,5m/sec and a significant wave height of fewer than 1.2 meters. Furthermore, the uniformity of the lithology along the route is the other reason to select the second route. Finally, the concrete block analysis generated a minimum dimension of 75cm x 60cm x 30cm, and a free span of 3 meters is safe to absorb the uplift and drag forces acting on the pipe.